2022
DOI: 10.1038/s42256-021-00438-4
|View full text |Cite
|
Sign up to set email alerts
|

Geometry-enhanced molecular representation learning for property prediction

Abstract: Effective molecular representation learning is of great importance to facilitate molecular property prediction. Recent advances for molecular representation learning have shown great promise in applying graph neural networks to model molecules. Moreover, a few recent studies design self-supervised learning methods for molecular representation to address insufficient labelled molecules; however, these self-supervised frameworks treat the molecules as topological graphs without fully utilizing the molecular geom… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
230
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
2
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 288 publications
(279 citation statements)
references
References 38 publications
1
230
0
Order By: Relevance
“…Datasets and setup MoleculeNet [48] is a widely used benchmark for molecular property prediction, including datasets focusing on different levels of properties of molecules, from quantum mechanics and physical chemistry to biophysics and physiology. Following previous work GEM [13], we use scaffold splitting for the dataset and report the mean and standard deviation of the results for three random seeds.…”
Section: Molecular Property Predictionmentioning
confidence: 99%
See 2 more Smart Citations
“…Datasets and setup MoleculeNet [48] is a widely used benchmark for molecular property prediction, including datasets focusing on different levels of properties of molecules, from quantum mechanics and physical chemistry to biophysics and physiology. Following previous work GEM [13], we use scaffold splitting for the dataset and report the mean and standard deviation of the results for three random seeds.…”
Section: Molecular Property Predictionmentioning
confidence: 99%
“…D-MPNN [49] and AttentiveFP [50] are supervised GNNs methods. N-gram [51], PretrainGNN [22], GROVER [11], GraphMVP [26], MolCLR [12], and GEM [13] are pretraining methods. N-gram embeds the nodes in the graph and assembles them in short walks as the graph representation.…”
Section: Molecular Property Predictionmentioning
confidence: 99%
See 1 more Smart Citation
“…Existing domain-specific PTMs mainly lie in the domain of healthcare [1,14], biomedical [8,10,16], and academic & research [2]. Most of them learn the domain-specific knowledge by pre-training on domain-specific corpora with the MLM pre-training task.…”
Section: Domain-specific Ptmsmentioning
confidence: 99%
“…Geometric deep learning, which encompasses deep neural networks operating on non-Euclidean domains (Bronstein et al, 2017), has shown considerable benefits in representation learning on proteins (Zhang et al, 2022; Jing et al, 2021; Gligorijević et al, 2021; Hermosilla et al, 2021) and other molecular structures (Fang et al, 2022; Townshend et al, 2021), particularly in the context of drug discovery (Gaudelet et al, 2021; Méndez-Lucio et al, 2021).…”
Section: Introductionmentioning
confidence: 99%